Who gets what? the new politics of insecurity - Rosenbluth, Frances McCall 1958-; Weir, Margaret 1952- (SSRC anxieties of democracy, 2021)
The authors of this timely book, Who Gets What?, harness the expertise from across the social sciences to show how skyrocketing inequality and social dislocation are fracturing the stable political identities and alliances of the postwar era across advanced democracies. Drawing on extensive evidence from the United States and Europe, with a focus especially on the United States, the authors examine how economics and politics are closely entwined. Chapters demonstrate how the new divisions that separate people and places-and fragment political parties-hinder a fairer distribution of resources and opportunities. They show how employment, education, sex and gender, and race and ethnicity affect the way people experience and interpret inequality and economic anxieties. Populist politics have addressed these emerging insecurities by deepening social and political divisions, rather than promoting broad and inclusive policies